On-surface synthesis of polyazulene with 2, 6-connectivity. Issue 89 (24th October 2019) - Sun, Qiang; Hou, Ian Cheng-Yi; Eimre, Kristjan; Pignedoli, Carlo A.; Ruffieux, Pascal; Narita, Akimitsu; Fasel, Roman
Abstract : We report the on-surface synthesis and characterization of the homopolymer of azulene connected exclusively at the 2, 6-positions. Abstract : Azulene, the smallest neutral nonalternant aromatic hydrocarbon, serves not only as a prototype for fundamental studies but also as a versatile building block for functional materials because of its unique opto(electronic) properties. Here, we report the on-surface synthesis and characterization of the homopolymer of azulene connected exclusively at the 2, 6-positions using 2, 6-diiodoazulene as the monomer precursor. As an intermediate to the formation of polyazulene, a gold-(2, 6-azulenylene) chain is observed.